Eltrombopag Preserves the Clonogenic Potential of Hematopoietic Stem Cells During Treatment With Antithymocyte Globulin in Patients With Aplastic Anemia - Margherita Vieri; Benjamin Rolles; Maria Crocioni; Mirle Schemionek-Reinders; Susanne Isfort; Jens Panse; Tim H. Brümmendorf; Fabian Beier (HemaSphere, 2023)
Aplastic anemia (AA) is frequently caused by a T-cell mediated autoimmune depletion of the hematopoietic stem and progenitor cell (HSPC) compartment. Immunosuppressive therapy (IST) with antithymocyte globulin (ATG) and cyclosporine represents the first-line treatment of AA. One side effect of ATG therapy is the release of proinflammatory cytokines such as interferon-gamma (IFN-γ), which is considered a major factor in the pathogenic autoimmune depletion of HSPC. Recently, eltrombopag (EPAG) was introduced for therapy of refractory AA patients due to its ability to bypass IFN-γ-mediated HSPC inhibition among other mechanisms. Clinical trials have evidenced that EPAG started simultaneously with IST leads to a higher response rate compared with its later administration schedules. We hypothesize that EPAG might protect HSPC from negative effects of ATG-induced release of cytokines. We observed a significant decrease in colony numbers when both healthy peripheral blood (PB) CD34+ cells and AA-derived bone marrow cells were cultured in the presence of serum from patients under ATG treatment, as compared with before treatment. Consistent with our hypothesis, this effect could be rescued by adding EPAG in vitro to both healthy and AA-derived cells. By employing an IFN-γ neutralizing antibody, we also demonstrated that the deleterious early ATG effects on the healthy PB CD34+ compartment were mediated at least partially by IFN-γ. Hence, we provide evidence for the hitherto unexplained clinical observation that concomitant use of EPAG in addition to IST comprising ATG leads to improved response in patients with AA.